1147 Renal Impairment by Indomethacin for PDA in VLBW Infants. (October 2012) - Kim, YJ; Lee, JY; Kim, C; Shin, SH; Son, SH; Choi, KY; Lee, JA; Choi, CW; Kim, EK; Kim, HS; Kim, BI; Choi, JH
Abstract : The Aims of our study were to identify the risk factors of using indomethain to very low birth weight infants (VLBWIs) during treatment of PDA. A retrospective review was undertaken of 95 VLBWIs who were born between January, 2008 and December, 2009, at Seoul National University Hospital NICU. Of the 158 infants, 103 infants were treated with indomethacin and 8 were excluded because one's mother had azotemia and 7 patients died within the first week of life. Patients were classified by renal insufficiency (RI) and normal renal function (NRF) group. RI group was defined as having oliguria or elevation of serum creatinine level over from 1 st dose of indomethacin administration until 2 days after finishing the course. Fourty-nine infants were RI group and 46 were NRF group. Administration duration was longer (2.5±2.0 days vs. 1.5±1.1 days, p=0.007) and number of dosages (5.1±2.8 days vs. 4.0±2.2 days, p=0.048) and cumulative dose were higher in RI group (0.85±0.52 mg/kg vs. 0.64±0.44 mg/kg p=0.040). Most of the clinical characters were not different between groups but dopamine administration rate (28.6% vs. 8.7%; p=0.013) and serum potassium level before administration of indomethacin (6.1±1.5 mEq/L vs. 5.1±1.6 mEq/L p=0.005) were significantly elevated in RI group. Hyperkalemia before administrating indomethacin and frequency/dose of indomethacin are related to occurrences of RI during indomethacin administration. Therefore, renal function monitoring and combined drugs which can influence the renal function should be monitored during treatment of PDA.